Coming of age with the New Republic, 1938-1950 - Peterson, Merrill D. (University of Missouri Press, 1999)
"In this memoir, Merrill D. Peterson traces his progress from a young Kansas Republican to a "Left Liberal" Democrat by reconstructing how the New Republic singularly influenced his intellectual development and academic career during some of the most turbulent years in American history - the final years of the Great Depression through World War II and the beginnings of the Cold War, Peterson recalls how, as a young man, he was guided to intellectual maturity by such extraordinary individuals as Max Lerner, Archibald MacLeish, Vincent Sheean, Alfred Kazin, Lewis Mumford, and Malcolm Cowley - all contributors to this important magazine. We look back, with Peterson, and see how their views are inextricably reflected in his own developing worldview."--Jacket